Assessment of risk factors for the development of musculoskeletal disorders among working women - Shettar, Deepti; Sherkhane, Mayur S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Musculoskeletal disorders (MSDs) account for 33% of all work-related illnesses and are the most frequent cause of all health-related absence from work. Working women particularly are at more risk of developing MSDs since they are involved in household activities and childcare along with office work. Psychosocial stress and comfort level at work also play a major role in development of MSDs. So, this study was done to assess the risk factors for the development of MSDs. Methods: Cross sectional study was conducted among 60 women clerical staff of a tertiary care hospital, who participated on voluntary basis. Data was collected using semi structured questionnaire. Information on MSDs was collected using Nordic scale. Descriptive statistics, chi square and odds ratio was used for data analysis. Results: Mean age of study participants was 33.88±6.97 years and mean BMI was 23.74±4.15 kg/m2. 81.7% were working 6-8 hours per day, 36.7% working in static posture for longer periods and 28.3% had sleep disturbances. Majority of women had low back pain both in last seven days (56.7%) and twelve months (35.0%). Those who complained of sleep disturbance were nine times and seven times at higher risk of developing pain in last seven days (p=0.015, OR=9.48) and twelve months (p=0.005, OR=7.85). Conclusions: Low-back pain was commonest among MSDs, significantly associated with sleep disturbance. Counseling sessions should be conducted regarding work ergonomics and Occupational Health Departments should be established to avoid untoward events that develop in their productive life.